The role of dermal fibroblasts in autoimmune skin diseases - Shi, Zeqi; Liu, Zhong; Wei, Yujia; Zhang, Ri; Deng, Yunhua; Li, Dong (Frontiers in Immunology, 2024)
Fibroblasts are an important subset of mesenchymal cells in maintaining skin homeostasis and resisting harmful stimuli. Meanwhile, fibroblasts modulate immune cell function by secreting cytokines, thereby implicating their involvement in various dermatological conditions such as psoriasis, vitiligo, and atopic dermatitis. Recently, variations in the subtypes of fibroblasts and their expression profiles have been identified in these prevalent autoimmune skin diseases, implying that fibroblasts may exhibit distinct functionalities across different diseases. In this review, from the perspective of their fundamental functions and remarkable heterogeneity, we have comprehensively collected evidence on the role of fibroblasts and their distinct subpopulations in psoriasis, vitiligo, atopic dermatitis, and scleroderma. Importantly, these findings hold promise for guiding future research directions and identifying novel therapeutic targets for treating these diseases.